KAJIAN SOSIAL EKONOMI PETANI PADI SAWAH DI KELURAHAN TARATARA TI-GA KECAMATAN TOMOHON BARAT KOTA TOMOHON (Socio-Economic Study of Paddy Rice in Taratara Tiga Village, Tomohon Barat District, Tomohon City) - Esther Pangemanan; Melsje Y. Memah; Noortje M. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The objective of this study is to observe the socio-economic conditions of rice farmers in Taratara Tiga Village, Tomohon Barat Sub District, Tomohon City. This research uses a descriptive method. The total population of 264 KK rice farmers, taken 10% (26KK). Data collection is done by interview technique. The data obtained from the results of the study were processed by using Qualitative analysis, and Quantitative analysis to determine the socio-economic condition of rice farmers in Taratara Tiga Village, Tomohon Barat Sub District, Tomohon City.       The research result showed that: (1) The average farmer is classified as being unproductive, (2) The average farmer education level is low, (3) The average condition of the farmer house is good, (4) Farmer has a relatively low income with an average income of  Rp. 1.000.000 – 2.000.000 in one harvest, (5) On average farmers have dependents of 3-5 people in one family, (6) Farmer have an average area of lowland rice in Taratara Tiga Village in the amount of  0,5-1 hectares, (7) On average farmers have lowland rice alone.Keywords: Socio-Economic Conditions, Rice Farmers